Decorating the Palki - Mumbai Archive Project Team (Jio Institute, 2024)
A silver palki (palanquin) is elaborately decorated with flowers, fabrics, and other artistic elements. This decoration is a form of cultural expression, showcasing local art and craftsmanship.